A Rapid Spatial Carrier-Frequency Phase-Shifting Method Based on the Orthogonality of Diamond Diagonal Vectors - Xiang Qiu; Liyun Zhong; Bingbo Li; Shengde Liu; Yunfei Zhou; Jiaxiang Xiong; Jindong Tian; Xiaoxu Lu (IEEE Photonics Journal)
From a one-frame off-axis interferogram with unknown carrier-frequency, a rapid spatial carrier-frequency phase-shifting (SCFPS) method is proposed to achieve the phase measurement of the dynamic process. First, based on the SCFPS technique, four-frame phase-shifting subinterferograms are constructed from one-frame off-axis interferogram. Second, by using the orthogonality of diamond diagonal vectors, respectively, achieved through the subtraction and addition operations between two equal length vectors, which are generated from above four-frame phase-shifting subinterferograms, the accurate phase can be retrieved rapidly. Compared with current SCFPS methods, in addition to maintaining high accuracy of phase-shifting method, as well as no requirement for carrier-frequency calibration, the proposed method reveals an obvious advantage in processing speed of phase retrieval, and this will greatly facilitate its application prospect for dynamic phase measurement.